BELBOG‘LI KURASH BO‘YICHA KATTALAR VA O‘SMIRLAR O‘RTASIDAGI JAHON CHEMPIONATI NATIJALARI TAHLILI (2021-yil bo’yicha) - Isayev, I.B. (SCIENCE and SOCIETY, 2022)
This article analyzes the results of the World Belt Wrestling Championship. It examines the successes and failures of our country’s belt wrestlers, world belt wrestling stars, as well as new winners in each weight category. The article focuses on the classic and freestyle trends of belt wrestling, as well as all weight categories in the women’s team.